2020
DOI: 10.1021/acsami.0c03404
|View full text |Cite
|
Sign up to set email alerts
|

Antiangiogenic Effect of Graphene Oxide in Primary Human Endothelial Cells

Abstract: In this work, we exploited an integrated approach combining systematic analysis of cytotoxicity, angiogenic potential, and metabolomics to shed light on the effects of graphene oxide (GO) on primary human endothelial Huvec cells. Contrary to the outcomes observed in immortalized cell lines able to internalize a similar amount of GO, significant toxicity was found in Huvec cells at high GO concentrations (25 and 50 μg/mL). In particular, we found that the steric hindrance of GO intracellular aggregates perturbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 71 publications
1
18
0
Order By: Relevance
“…GO nanoplatelets improve anti-cancer effect of cisplatin on human lung cancer cells [24]. It has been found GO induces anti-angiogenic impact of GO in primary human endothelial cells [25].…”
Section: Discussionmentioning
confidence: 99%
“…GO nanoplatelets improve anti-cancer effect of cisplatin on human lung cancer cells [24]. It has been found GO induces anti-angiogenic impact of GO in primary human endothelial cells [25].…”
Section: Discussionmentioning
confidence: 99%
“…A considerable antiangiogenic effect of GO in primary human endothelial Huvec cells was due to the combination of the physical hindrance of internalized GO aggregates, induction of oxidative stress, and alteration of some metabolic pathways. Besides, steric hindrance of GO intracellular aggregates, perturbing the correct assembly of cytoskeleton and distribution of mitochondria and causing impairment of cell migration, affected the formation of capillary-like structures and the consumption of niacinamide, which is a precursor of energy carriers, as well as several amino acids involved in the regulation of angiogenesis [ 128 ].…”
Section: Gbns As Drugs and Nanocarriersmentioning
confidence: 99%
“…182 Similarly, in a more recent study, GO showed an anti-angiogenesis effect on HUVECs through the induction of oxidative stress and the manipulation of some metabolic pathways. 183 Focusing on the strong correlation between the level of ROS and NF-κB activation, the NF-κB related anti-angiogenesis effect of graphite nanoparticles and graphene oxide nanoplatelets (nGO) was assessed on both p53 mutant and wild type of glioblastoma cancer cells. The treatment of HUVECs co-cultured with p53 wild type of glioblastoma (U87) attenuated their strength for angiogenesis but not for p53 mutant group (U118).…”
Section: Angiogenesis and Anti-angiogenesis Ability Of Graphenementioning
confidence: 99%